Clinical performance of restorative materials in primary molar teeth - Harun, Nor Asilah; Yaacob, Munirah; Abdul `Alim, Mohamad Shafiq Aizuddin; Ghazali, Saifullah; Nik Khairuzaman, Nik Khairul Azmi (Elsevier, 2019)
The aim of this study is to determine the clinical performance of primary molar restorations placed among paediatric patients at the Polyclinic, Kulliyyah of Dentistry, IIUM. A total of 99 primary molar restorations were evaluated clinically using the modified United States Public Health Service criteria. Amalgam restorations (104 weeks) showed the highest survival time followed by glass ionomer (87 weeks), composite (84 weeks) and stainless steel crown (79 weeks). Glass ionomer showed the highest survival time for class I but for class II, it was amalgam. This results indicates that the type of material influences the survival rate of restorations.